2009
DOI: 10.1002/pits.20440
|View full text |Cite
|
Sign up to set email alerts
|

Working conditions as risk or resiliency factors for teachers of students with emotional and behavioral disabilities

Abstract: This pilot study examined working conditions reported by special education teachers of students with emotional and behavioral disorders (EBD) to identify factors common to teachers likely to leave their positions within the next 2 years and factors common to those likely to stay. Survey responses from an international sample of 776 teachers and related services providers indicated administrative support, availability of support personnel, access to curricula, adequate time for paperwork, years of teaching stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
125
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(142 citation statements)
references
References 4 publications
11
125
3
1
Order By: Relevance
“…This finding is remarkable as teaching children with psychiatric problems is often regarded as a challenging task (Greene et al, 2002) and research has shown that children's misbehavior is related to higher levels of burnout and lower levels of perceived competence (Tsouloupas, Carson, Matthews, Grawitch, & Barber, 2010). However, classroom adaptations that are available in segregated settings for special education, such as additional resources for teachers, special teacher training, and smaller class size (Albrecht, Johns, Mounsteven, & Olorunda, 2009;Meijer, 2003), may support teachers to meet their needs and the needs of students with psychiatric problems.…”
Section: Discussionmentioning
confidence: 81%
“…This finding is remarkable as teaching children with psychiatric problems is often regarded as a challenging task (Greene et al, 2002) and research has shown that children's misbehavior is related to higher levels of burnout and lower levels of perceived competence (Tsouloupas, Carson, Matthews, Grawitch, & Barber, 2010). However, classroom adaptations that are available in segregated settings for special education, such as additional resources for teachers, special teacher training, and smaller class size (Albrecht, Johns, Mounsteven, & Olorunda, 2009;Meijer, 2003), may support teachers to meet their needs and the needs of students with psychiatric problems.…”
Section: Discussionmentioning
confidence: 81%
“…The extensive literature on staff turnover has provided the field with consistent and meaningful insights into factors that could enhance the retention of professionals. Examples of influential factors on the individual level are low salaries (Colton & Roberts, 2004), the balance between work and personal life (Smith, 2005), job moral and job satisfaction (Colton, 2005), the perceptions of the children and youth cared for (Colton & Roberts), and behaviour management approach (Albrecht et al, 2009). Examples of influential factors on the organisational level are training (Colton, 2005;Colton & Roberts, 2004), administrative support and adequate time for paperwork (Albrecht et al, 2009), the implementation of evidence-based practices (Aarons et al, 2009), and supervision, both by supervisors (Cearly, 2004;Colton & Roberts, 2007;Gersten at al., 2001;Smith, 2005) as well as by peers (Colton & Roberts, 2007;Gersten et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Due to a lack of specialized expertise, teachers often feel as if the inclusion of special populations adds stress to the work environment, because teachers have not been adequately trained to meet the diverse needs of the students in the classroom (Buell, Hallam, Gamel-McCormick, & Scheer, 1999). General education teachers have expressed a lack in their own understanding and ability to teach students with varying disabilities, especially students with emotional and behavior disorders (Albrecht, Johns, Mounsteven, & Olorunda, 2009). Teachers lack the skills to manage multiple behavior episodes.…”
Section: Turn Around the Lowest Achieving Schoolsmentioning
confidence: 99%
“…Teachers in these populations also have higher attrition rates and teacher turnover rates and have reported lower perceptions of student behavior (Albrecht et al, 2009). Teachers in these schools are often teachers new to the profession and lack the skills needed to build classroom routines, systems, and structures.…”
Section: Turn Around the Lowest Achieving Schoolsmentioning
confidence: 99%
See 1 more Smart Citation